Spontaneous Orientation Polarization of Anisotropic Equivalent Dipoles Harnessed by Entropy Engineering for Ultra-Thin Electromagnetic Wave Absorber - Honghan Wang; Xinyu Xiao; Shangru Zhai; Chuang Xue; Guangping Zheng; Deqing Zhang; Renchao Che; Junye Cheng (Nano-Micro Letters)
Highlights The strengthening mechanism of spontaneous orientation polarization of anisotropic equivalent dipoles within high-entropy alloys (HEAs) is proposed for enhancing dielectric attenuation of HEAs. The source of carbon supporter is expanded to the biomass category, which can construct the shell-core heterointerfaces with HEAs by means of a reformative carbothermal shock method. The sample carbonized cellulose paper/HEAs-Mn2.15 achieves efficient electromagnetic wave absorption of -51.35 dB at an ultra-thin thickness of 1.03 mm. This work combines theoretical calculations and electromagnetic simulations to propose feasible strategies for the design and application of electromagnetic functional devices such as ultra-wideband bandpass filter.